World Heritage Status and Farmers' Income: Evidence From a Regression Discontinuity Design in Colombia - Orlando Rodríguez; Maria Vrachioli; David Wüpper; Johannes Sauer (Agricultural Economics, 2025)
The core of Colombia's coffee growing region was designated as a World Heritage (WH) site in 2011, making a distinction between “the core” of the region and “the periphery.” However, the coffee cultural heritage does not abruptly stop at the WH boundary but it exists inside and outside the boundary. This allows us to use a regression discontinuity design (RDD) to identify the income effect for farmers located just inside the WH site. We find that the WH designation of the region increases coffee farmers' income by up to 757 per month. The mechanism includes more tourism activities inside the coffee farms by 39%, higher adoption of sustainable farming practices, increasing organic coffee production by 8.38%, and increasing payments for environmental services (PES) by 2.35%.
Keywords: 330; coffee production; regression discontinuity; world heritage